Teaching character education through literature : awakening the moral imagination in secondary classrooms / Karen E. Bohlin. - Bohlin, Karen E. (Teaching character education., 2005)
This book offers guidance for teachers looking to include character education within their lessons. It demonstrates how teachers can provide an encounter with literature that enables students to be more responsive to ethical themes and questions.